PERRSEPSI SISWA TERHADAP PENGGUNAAN CORPUS TOOLKIT DALAM PEMBELAJARAN GRAMMAR BAHASA INGGRIS - Abdul Muis Muhyidin (Jurnal Guru Dikmen dan Diksus, 2021)
English grammar learning has been widely used through deductive teaching grammar. Students were trained to be introduced by knowing grammar patterns. Thus they were stimulated to memorize them. However, English learning grammar needs to be equipped with the real language used. It could be bridged by spoken corpus. As the spoken corpus is under-explored, this present research aimed at exploring students' perceptions toward the implementation of the spoken corpus in English grammar learning applied in the Vocational English classroom. The research involved the students from electrical engineering as research participants. Six students out of thirty-six were agreed to be interviewed. The basic interpretative study used as the design of this research as the students explored their learning experiences. The result illustrated that corpus toolkit mediated students actively engaged, delighted, and enthusiastic in learning grammar; spoken English words used in learning grammar through the corpus toolkit motivated students to speak English; the corpus toolkit met the students need to learn during the COVID-19 pandemic. The implications of this present research while the Pandemic situation potentially contributed to the students having accessible learning and met their needs during the COVID-19 pandemic.